PENANAMAN POHON SEBAGAI UPAYA MENJAGA CADANGAN AIR TANAH DAN MENCEGAH BAHAYA EROSI DI KECAMATAN CIBIRU - Kundang Harisman; Budy Frasetya; Adjat Sudrajat; Suryaman Birnadi; Maratun Sholeha (Pusat Pengabdian kepada Masyarakat LP2M UIN Sunan Gunung Djati Bandung, 2019)
Land use conversion in to settlements and agricultural land affect rainwater can not be infiltrate directly in to the soil. Cibiru District has large area with slope so that this region has high risk of erosion. Soil and water conservation activity through tree planting methode involving comunity services is startegic effort to overcome potential erosion hazzard and increase soil infiltration. The activity of Community services was held from July-August 2018 in Palasari sub-district which has slope 8-15%. This community services methode used in the form of tree planting workshop and supervision during the manintenance periode. This tree planting program was welcomed enthusiastically by the community. The comunity in Cibiru District is pro active in preservation trees, especially during the dry season.